Enforcing current-state opacity through shuffle in event observations - Barcelos, Raphael Julio (2018)
Opacity is a property that ensures that a secret behavior of the system is kept hidden from an Intruder. In this work, we deal with current-state opacity, and propose an Opacity-Enforcer that is able to change, in an appropriate way, the order of observation in the event occurrences in the system, so as to mislead the Intruder to always wrongly estimate at least one non-secret state. A necessary and sufficient condition for the feasibility of the Opacity-Enforcer synthesis is presented and also two algorithms to build the automaton that realizes such an enforcement.